2000
DOI: 10.1159/000016771
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapies in Hepatology: Liver-Directed Gene Transfer and Hepatocyte Transplantation

Abstract: Gene transfer and epithelial cell transplantation technologies play an important role in the development of new therapeutic concepts for liver diseases. Although liver organ transplantation has revolutionized the treatment of a wide spectrum of acute and chronic liver diseases, gene- and cell-based therapies are emerging at an astonishing pace, because they promise to be less invasive, less costly and at least as effective as currently established therapy protocols. Experimental gene therapy models have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…The interest in hepatic stem cells shifts currently from a proposed involvement in liver carcinogenesis toward the field of experimental therapies for liver diseases: (1) for hepatocyte transplantation and hepatic tissue engineering concepts as a new source for liver tissue and (2) as promising target cells for somatic gene therapy of enzyme deficiency-based metabolic liver diseases. [40][41][42][43][44] A first animal study showed a possible application of isolated fetal hepatocytes for the correction of a metabolic disorder; the intrasplenic transplantation of normal fetal hepatocytes in analbuminemic rats led to a repopulation of the diseased liver with healthy donor hepatocytes and a normalization of albumin levels. 45 The role of fetal liver stem cells for new therapeutic applications has yet to be defined; in addition to the theoretical risks from the use of undifferentiated cells, the legal and ethical issues have to be addressed in the scientific community.…”
Section: Do Putative Hepatic Stem-like Cells Exist During Fetal Livermentioning
confidence: 99%
“…The interest in hepatic stem cells shifts currently from a proposed involvement in liver carcinogenesis toward the field of experimental therapies for liver diseases: (1) for hepatocyte transplantation and hepatic tissue engineering concepts as a new source for liver tissue and (2) as promising target cells for somatic gene therapy of enzyme deficiency-based metabolic liver diseases. [40][41][42][43][44] A first animal study showed a possible application of isolated fetal hepatocytes for the correction of a metabolic disorder; the intrasplenic transplantation of normal fetal hepatocytes in analbuminemic rats led to a repopulation of the diseased liver with healthy donor hepatocytes and a normalization of albumin levels. 45 The role of fetal liver stem cells for new therapeutic applications has yet to be defined; in addition to the theoretical risks from the use of undifferentiated cells, the legal and ethical issues have to be addressed in the scientific community.…”
Section: Do Putative Hepatic Stem-like Cells Exist During Fetal Livermentioning
confidence: 99%
“…Nevertheless, cell-based therapies are emerging as an alternative to whole-organ transplantation. Hepatocyte transplantation has been used to bridge patients to whole-organ transplantation [7,69], to decrease mortality in acute liver failure [18,58], and for treatment of metabolic liver disease [3,16,19,22,29,30,47,48,66,67,69]. Cell transplantation is less invasive than whole-organ transplantation and can be performed repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…3 In view of these shortfalls, cell-based hepatocyte transplantation is of particular interest and believed to hold great promise because of the simpler and less invasive procedure. A single donor could serve multiple recipients, and excess cells could be cryopreserved for future use.…”
mentioning
confidence: 99%